A Case of Undifferentiated Carcinoma in a 2-Month Postpartum Reproductive Tract with a Rapid and Fulminant Course. (19th October 2021) - Yokoyama, Yasuhiro; Suzuki, Mariko; Sato, Yasumasa; Iwagaki, Shegenori; Takahashi, Yuichiro; Iwata, Hitoshi
Abstract : Advanced carcinoma of the lower female reproductive tract is rare during pregnancy and the postpartum period. We here present a case of a 32-year-old Japanese woman, whose entire lower reproductive tract had been invaded by carcinomas as of 2 months after childbirth. She had been infertile, and pregnancy had been established by repeated embryo transfer. The gynecological cancer screening, which included Pap smear tests, was negative during the periods she underwent infertility treatment or during the first trimester. At 26 gestational weeks, the patient noticed uterine contractions concomitant with genital bleeding. Labor progressed slowly and steadily; thus, the pregnancy was ended by cesarean section at 29 weeks. At 2 months after childbirth, the patient experienced increased left abdominal pain and underwent a pelvic examination, revealing multiple pelvic masses and diffuse vaginal tumors causing stenosis. Vaginal tumors were biopsied, and histochemical analysis showed undifferentiated carcinoma with possible adenocarcinoma. Imaging modalities including CT, MRI, and PET-CT suggest that the carcinoma had invaded the entire reproductive tract, especially the uterine body, metastasized into the lungs and the ischial bones, and disseminated onto the peritoneum. She received multiple rounds of chemotherapy but died 6 months after childbirth. Taking into consideration the clinical feature and immunohistochemical profiles of the cancer cells, the endometrium is the most likely origin.